2007
DOI: 10.1002/lapl.200710077
|View full text |Cite
|
Sign up to set email alerts
|

High-power, continuous-wave, Nd:LuVO4 microchip lasers

Abstract: Nd:LuVO 4 crystal was used for the most compact and the simplest laser, i.e. the microchip construction. LD (laser diode)-pumped, continuous-wave output property was detected on several Nd:LuVO 4 microchips with different Nd 3+ doping level, crystal length, and transmittance of output surface. With a 0.5 at.%, 1.5 mm, T = 1% crystal, 9.7 W maximum output was achieved, corresponding an optical-optical conversion efficiency of 32.0%. With a 1 at.%, 1.5 mm, T = 1% crystal, 9.1 W maximum output was achieved at a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…And the intrinsic loss of Nd:GGG crystal was measured to be 0.86% cm −1 in our experiment. [1][2][3][4][5][6][7]. Gadolinium gallium garnet (GGG), another crystal suitable for Nd doping and first grown by J.…”
Section: Introductionmentioning
confidence: 99%
“…And the intrinsic loss of Nd:GGG crystal was measured to be 0.86% cm −1 in our experiment. [1][2][3][4][5][6][7]. Gadolinium gallium garnet (GGG), another crystal suitable for Nd doping and first grown by J.…”
Section: Introductionmentioning
confidence: 99%
“…[10]. In that work we found that the specification of Nd:LuVO 4 microchips had very obvious infection on the laser output result.…”
Section: +mentioning
confidence: 92%
“…A new member of Nd-doped vanadate family, Nd:LuVO 4 [8][9][10][11][12], has attracted considerable attentions recently. Actively and passively Q-switched Nd:LuVO 4 lasers [13], mode locking Nd:LuVO 4 lasers [14,15] and optical parameters oscillator by a Q-switched Nd:LuVO 4 lasers [16] :YAG has become the most important saturable absorber due to its high damage threshold and large thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%